Energy Safety Position in the National Security of the Country - Nurtayeva, Gulmira; Aikumbekov, Nurlan (DIXI, 2019)
In this article, we would like to define and research the energy safety position in the national security of the country. Many questions are submitted for legal support, especially regarding the cooperation between the state and the private economy sector, directed to regulate cooperation in the energy market, also warranties establishment and regulatory actions on private entrepreneurs in case of emergency; and also questions regarding the state responsibility in case of loss being inflicted because of cost adjustment. Action mechanism is not developed by the state in case of safety risk appearing, of quasisector and private economy sector subjects, and direct or indirect regulating actions are not regulated. As a result, in case of according safety risk appears, “energy blockade” or “embargo of the state” will appear with many additional questions which are without a legal provision in the current legal regulatory acts. Taking into consideration that the questions should be dealt with will hold out a long process, so our opinion should be started right now in the period of stable development of the country and absence of considering safety risk. Indeed otherwise, we can face huge problems in the meantime without a sharp regulated plan of measurements and actions of fuel and energy sector cooperation between the people and the state.